Occurrence and germination of dinoflagellate cysts in surface sediments from the Red Sea off the coasts of Saudi Arabia - Zakaria A. Mohamed; Abdulrahman M. Al-Shehri (Oceanologia, 2011)
The distribution and abundance of dinoflagellate cyst assemblages were investigated in surface sediments from south-western Red sea coasts of Saudi Arabiaat six sites during March 2010. A total of 19 taxa of dinoflagellate cysts were identified from all sites. The sampling sites showed a similar cyst assemblage, but theydiffered in total cyst abundance (3 to 4083 cysts g-1 dry weight). Cyst abundance was strongly correlated with sediment characteristics, the highestnumbers being recorded in sediments with large contents of organic carbon, silt and clay. Cyst assemblages were dominated by cysts of potentially toxicspecies, including Cochlodinium polykrikos, Prorocentrum minimum, Dinophysis acuminata, Alexandrium catenella and Scrippsiellatrochoidea. Most cysts germinated successfully at different rates at 15 and 25°C. This study suggests that surface sediments from all Saudi Red Seacoasts should be monitored for the presence of dinoflagellate cysts to give ample warning of the presence and abundance of toxic species in a given area.